Isolated tricuspid regurgitation secondary to annular dilatation: a rare case report - S Joshi, Kavita; Bajpai, Smrati; Pazare, AR (International Journal of Medical Research and Review, 2016)
Isolated tricuspid regurgitation (TR) which is due to primary valvular pathology is a rare occurrence. Very few cases have been reported from India. Pathology may involve tricuspid valve leaflets, subvalvular apparatus or valve annulus. Tricuspid regurgitation is usually functional and associated with rheumatic heart disease or dilated cardiomyopathy. Here we are presenting a case of 55 years old man with primary tricuspid regurgitation secondary to dilatation of tricuspid annulus. Patient was started on diuretics and anticoagulation, 50% reduction in symptoms was noted after one week of treatment. In the given clinical context cause of this isolated tricuspid regurgitation appears to be secondary to annular dilatation. Patient was referred for myocardial biopsy and Annuloplasty. Patient’s course seems to be rapidly progressive once he presents with the symptoms. But with the advances in percutaneous interventions there is a hope for these patients to be treated with significant clinical improvements.